Improving Children’s Cognitive Skills Through the Stone in Early Childhood (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2022)
This study aims to determine whether cognitive abilities be increased through stone media in early childhood. The formulation of the problem in this study is whether cognitive ability can be increased through stone media in Fathina Kindergarten. The subjects or informants of the study were children from the Fathina Kindergarten, Majene Regency, as many as 20 people. This research was carried out in the odd semester of the 2021/2022 academic year, which took place from August to October and was carried out at Fathina Kindergarten, Majene Regency. The Concept of addition and subtraction through stone media at Fathina Kindergarten, Majene Regency, is experimental classroom action research (CAR). Experimental classroom action research is classroom action research conducted by trying to apply various techniques/strategies effectively and efficiently in a teaching and learning process activity, in this case, through the assignment method. Based on the results of research that has been carried out in Group B of Fathina Kindergarten with 20 students, increasing the ability through stone media has increased with the percentage value of 80%. From the results of the Classroom Action Research conducted by the researcher, namely increasing the ability through stone media, it can increase in Group B in Fathina Kindergarten.